2018
DOI: 10.1016/j.jsat.2018.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Mobilizing community support in people receiving opioid-agonist treatment: A group approach

Abstract: This descriptive study evaluates a novel group intervention designed to help opioid-dependent patients in medication-assisted treatment identify and recruit drug-free individuals to support recovery efforts. The Social Network Activation Group works with patients who are actively using drugs and resistant to including drug-free family or friends in treatment. The group encourages patients to attend structured recovery, religious, or recreational activities in the community to find recovery support. For those w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Perhaps patients valued privacy over the potential benefits of enlisting support. Based partly on this response, we developed a group intervention that uses motivational interviewing principles to help patients resolve ambivalence regarding significant other participation 26 . Incorporating telehealth strategies 27 might improve rates of participation for those worried about time commitment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Perhaps patients valued privacy over the potential benefits of enlisting support. Based partly on this response, we developed a group intervention that uses motivational interviewing principles to help patients resolve ambivalence regarding significant other participation 26 . Incorporating telehealth strategies 27 might improve rates of participation for those worried about time commitment.…”
Section: Discussionmentioning
confidence: 99%
“…Based partly on this response, we developed a group intervention that uses motivational interviewing principles to help patients resolve ambivalence regarding significant other participation. 26 Incorporating telehealth strategies 27 might improve rates of participation for those worried about time commitment. A study evaluating reasons for disinterest might suggest strategies to improve intervention uptake.…”
Section: Feasibility and Acceptabilitymentioning
confidence: 99%
“…Prior to tailored treatment planning, the nature of social network support should be systematically assessed. Research provides additional evidence that many persons in substance use treatment possess non-substance using family or friends who are willing to support recovery efforts (153). Activating non-substance using family and friends has shown to provide potential pathways to help persons with SUDs access and benefit from community support (154,155).…”
Section: Discussionmentioning
confidence: 99%
“…This means separating from "friends" they used drugs with or who create feelings that trigger use, building up positive supports with sober people, like friends who are clean or solidly in recovery, a sponsor, or supportive family members. Research has shown that the addition of a sober partner in recovery greatly facilitated successful recovery [5,6]. If a person knows that going to a bar, even if they don't drink, will make them want to get high, they need to avoid that situation.…”
Section: Identifying Triggersmentioning
confidence: 99%